2020
DOI: 10.1149/1945-7111/ab7d45
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of 2M5S and Its Influence on Reduction of Cu Pumping and Keep-Out Zone

Abstract: Previously, we have reported the low thermal expansion copper electrodeposited in solution containing 2-Mercapto-5benzimidazolesulfonic acid sodium salt dihydrate (2M5S). In this research, we investigated the electrochemical behavior 2M5S additive by CVS and LSV measurements. The 2M5S additive showed an inhibition effect during electrodeposition of copper, both in the absence and presence of Cl − . Using a combination of the 2M5S leveler with another SDDACC leveler and SPS accelerator, the thermal expansion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The study of the electrochemical behavior of 2M5S by V. Q. Dinh showed that 2M5S inhibits the copper deposition both in the absence and presence of Cl − . 8 However, in this case, the PEG inhibition effect is much stronger and suppresses the inhibition effect of 2M5S.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The study of the electrochemical behavior of 2M5S by V. Q. Dinh showed that 2M5S inhibits the copper deposition both in the absence and presence of Cl − . 8 However, in this case, the PEG inhibition effect is much stronger and suppresses the inhibition effect of 2M5S.…”
Section: Resultsmentioning
confidence: 86%
“…Dinh and K. Kondo. 1,8 They successfully reduced the TEC of copper from 17.2 × 10 −6 °C−1 to 14.5 × 10 −6 °C−1 by using 2 levellers sulfonated diallyl dimethyl ammonium chloride copolymer (SDDACC) and 2M5S. The reduction in copper TEC is explained by the incorporation of 2M5S into the electrodeposited copper.…”
mentioning
confidence: 99%
See 3 more Smart Citations